Evidence from the Hamburg City Health Study - association between education and periodontitis - Carolin Walther; Kristin Spinler; Katrin Borof; Christopher Kofahl; Guido Heydecke; Udo Seedorf; Thomas Beikler; Claudia Terschüren; Andre Hajek; Ghazal Aarabi (BMC, 2022)
Abstract Objective Large-scale population-based studies regarding the role of education in periodontitis are lacking. Thus, the aim of the current study was to analyze the potential association between education and periodontitis with state of the art measured clinical phenotypes within a large population-based sample from northern Germany. Material & methods The Hamburg City Health Study (HCHS) is a population-based cohort study registered at ClinicalTrial.gov (NCT03934957). Oral health was assessed via plaque-index, probing depth, gingival recession and gingival bleeding. Periodontitis was classified according to Eke & Page. Education level was determined using the International Standard Classification of Education (ISCED-97) further categorized in "low, medium or high" education. Analyses for descriptive models were stratified by periodontitis severity. Ordinal logistic regression models were stepwise constructed to test for hypotheses. Results Within the first cohort of 10,000 participants, we identified 1,453 with none/mild, 3,580 with moderate, and 1,176 with severe periodontitis. Ordinal regression analyses adjusted for co-variables (age, sex, smoking, diabetes, hypertension and migration) showed that the education level (low vs. high) was significantly associated with periodontitis (OR: 1.33, 95% CI: 1.18;1.47). Conclusion In conclusion, the current study revealed a significant association between the education level and periodontitis after adjustments for a set of confounders. Further research is needed to develop strategies to overcome education related deficits in oral and periodontal health.